Baakisimba: Gender in the Music and Dance of the Baganda People of Uganda. Sylvia A. Nannyonga-Tamusuza, 2005. 294 pp., 13 figures, 19 plates. New York: Routledge (Current Research in Ethnomusicology Series). Jennifer C. post, series editor. - Kruger, Jaco (International Library of African Music, 2007)
pages: 116-118
Keywords: Gender; Dance; Music; Ganda (African people); African Music; Uganda